2017
DOI: 10.1016/j.ccell.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

CHD4 Has Oncogenic Functions in Initiating and Maintaining Epigenetic Suppression of Multiple Tumor Suppressor Genes

Abstract: SUMMARY An oncogenic role for CHD4, a NuRD component, is defined for initiating and supporting tumor suppressor gene (TSG) silencing in human colorectal cancer. CHD4 recruits repressive chromatin proteins to sites of DNA damage repair, including DNA methyltransferases where it imposes de novo DNA methylation. At TSGs, CHD4 retention helps maintain DNA hypermethylation-associated transcriptional silencing. CHD4 is recruited by the excision repair protein OGG1 for oxidative damage to interact with the damage-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 41 publications
9
149
1
Order By: Relevance
“…We also found that MUC1-C upregulates expression of the ATPdependent CHD4 helicase by an MYC-dependent mechanism. CHD4 functions in nucleosome remodeling and in the repression of TSGs by recruitment of epigenetic effectors, such as DNMTs (11,45). As found for targeting MUC1-C (4), silencing CHD4 reactivates hypermethylated TSGs (45), supporting the potential importance of MUC1-C in integrating induction of DNMT3b and the CHD4 protein in the hypermethylation of TSGs.…”
Section: Discussionmentioning
confidence: 59%
“…We also found that MUC1-C upregulates expression of the ATPdependent CHD4 helicase by an MYC-dependent mechanism. CHD4 functions in nucleosome remodeling and in the repression of TSGs by recruitment of epigenetic effectors, such as DNMTs (11,45). As found for targeting MUC1-C (4), silencing CHD4 reactivates hypermethylated TSGs (45), supporting the potential importance of MUC1-C in integrating induction of DNMT3b and the CHD4 protein in the hypermethylation of TSGs.…”
Section: Discussionmentioning
confidence: 59%
“…CHD4, a chromodomain‐containing protein, catalyzes ATP‐dependent chromatin remodeling as a core component of the nucleosome remodeling and histone deacetylase (NuRD) repressor complex, which is involved in the epigenetic regulation of gene transcription, DNA repair, and cell cycle progression, and is a hallmark of virtually all human cancers . Furthermore, TWIST, a transcriptional regulator, interacts with several components of the NuRD complex, and the TWIST/NuRD complex plays an essential role in EMT and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that CHD3 and CHD4 are commonly mutated in a subset of breast cancers . Furthermore, a recent study revealed that CHD4 has an oncogenic role in maintaining epigenetic silencing of tumor suppressor genes in colorectal cancer (Xia et al, 2017). CHD7 expression predicts survival outcomes in patients with resected pancreatic cancer (Colbert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%